Sustainability Strategies and Organizational Performance of Selected Family-Led Businesses in Kenya - Mwaura, Charity; Mathenge, Paul; Mungai, Caroline (European Journal of Business and Strategic Management, 2023)
Purpose: The study sought to establish the effect of entrepreneurial sustainability strategies on organizational performance of family-led businesses in Kenya. Methodology: The descriptive research technique was used for this study and target population was the owners/ managers of the 277 family-led businesses in Kenya. The technique of stratified random sampling was applied to derive the 83 respondents. Questionnaires were used to obtain primary data and close-ended questions were used that were in the form of likert scales questions. Data collected was analyzed by use of descriptive and inferential statistics using SPSS Version 22. The descriptive statistics included frequency percentages, mean and standard deviations. A multiple regression model, correlation analysis and ANOVA was further carried out. Tables, pie charts and graphs were used for data presentation. Findings: There was a strong positive correlation of 0.764 between talent management and the performance of selected family-led businesses in Kenya. There was a moderate positive correlation of 0.469 between succession planning and the performance of selected family-led businesses in Kenya. There was a moderate positive correlation of 0.755 between innovation strategies and the performance of selected family-led businesses in Kenya. There was a moderate positive correlation of 0.362 between professionalization and performance of selected family-led businesses in Kenya. Unique Contribution to Theory, Practice and Policy: The study was guided by Family Systems theory and theory of Performance. The theories may be used to anchor future studies in the business sector The study recommends that family-led businesses should recruit competent employees, adopt and implement performance appraisals, conduct training sessions to improve employee skills and ensure they retain the employees through employee motivation. The study recommends that to improve on the performance of the businesses, the organizations should identify critical roles, build succession benches, and develop high-potential candidates for promotion. The study recommends that management of family led business should invest resources in innovations such as big data analytics and artificial intelligence to increase their competitiveness. The study recommends that the family lead business should ensure that they hire professionals and also conduct the recruitment exercise in a competitive and professional manner.